The Grammar of pattern / Michael Hann (Taylor & Francis Group, 2019)
The Grammar of Pattern describes characteristics of textile and other surface patterns, and identifies, illustrates, and reviews a wide range of pattern types including spotted, striped, checked, tessellating and other types of all-over patterns with original drawings and images. This book includes original black-and-white line drawings and color images. The modular nature of patterns is explored, and attention is focused on the vast diversity of pattern types which can emerge from a small inventory of components. The book features material that is easily accessible with obvious mathematical content kept to a minimum and offers fresh perspectives on the nature of tessellating and other all-over patterns. This book serves as an effective practical guide for both students and professionals. Select sample exercises and student assignments are included, making this an ideal course text for teachers engaged across the full range of design education.